In silico study of molecular mechanisms of action: Estrogenic disruptors among phthalate esters. (December 2019) - Zhu, Qian; Liu, Lanhua; Zhou, Xiaohong; Ma, Mei
Abstract: Phthalate esters (PAEs), as widely used plasticizers, have been concerned for their possible disruption of estrogen functions via binding to and activating the transcription of estrogen receptors (ERs). Nevertheless, the computational interpretation of the mechanism of ERs activities modulated by PAEs at the molecular level is still insufficient, which hinders the reliable screening of the ERs-active PAEs with high speed and high throughput. To bridge the gap, the in silico simulations considering the effects of coactivators were accomplished to explore the molecular mechanism of action for the purpose of predicting the estrogenic potencies of PAEs. The transcriptional activation functions of human ERα (hERα) modulated by PAEs is predicted via the simulations including binding interaction of PAEs and hERα, conformational changes of PAEs-hERα complexes and recruitment of coactivators. Molecular insight into the diverse estrogen mechanism of action among PAEs with regard to hERα agonists and selective estrogen receptor modulators (SERMs) is provided. Agonist-modulated conformational change of hERα leads to the optimal exposure of its Activation Function 2 (AF-2) surface which, in turn, facilitates the recruitment of coactivators, therefore promoting the transcriptional activation functions of hERα. Conversely, binding interaction of hERα with SERMs among PAEs leads to the conformational change with blocked AF-2 surface, thus preventing the recruitment of coactivators and consequently inhibiting the AF-2 activity. The two-hybrid recombinant yeast is experimentally used for verification. The established in silico evaluation methodology exhibits great promise to speed up the prediction of chemicals which work as hERα agonist or SERMs. Graphical abstract: Image 1 Highlights: An in silico method for the molecular mechanisms of estrogen receptors (ERs) transcriptional activities is developed. Using molecular docking and molecular dynamics simulations, 21 kinds of phthalate esters (PAEs) are analyzed. Molecular insight into PAEs as hERα agonists and selective estrogen receptor modulators is offered. The method exhibits great promise to speed up the prediction of chemicals as estrogenic disruptors.